Navigating precarious visibility: Ugandan sexual minorities on Twitter. (1st June 2019) - Strand, Cecilia
Although invisibility has historically provided a degree of protection, Lesbian, Gay, Bi-, Trans-, Queer and Intersexuals need to materialize publicly as a group to successfully advocate for their rights. Decades of systematic exclusion of the community from traditional discourse-producing sites, such as media and physical spaces, could potentially render self-controlled digital spaces an attractive alternative for human rights advocacy and self-representation. The following article explores to what degree the Ugandan sexual minority community utilizes the microblogging platform Twitter's inbuilt affordance of self-controlled visibility to counter and challenge pervasive homophobic discourses. Through a qualitative content analysis of a purposeful sample of tweets generated by the main sexual minority network (Sexual Minorities Uganda [SMUG]), during the latest general election, the study finds that the affordance of controlled visibility is not consistently exploited for disseminating alternative narratives to external audiences, but rather chooses to highlight the agency of SMUG and its network members.